Hubungan Faktor Lingkungan Fisik Dengan Kualitas Hidup Penderita Diabetes Mellitus - Tania Sepriani (Publikasi Indonesia, 2022)
Diabetes Mellitus (DM) is a chronic disease that can affect the quality of life. One of the factors that affect the quality of life is the physical environment, such as temperature, light, and distance from the house to the road. This study aims to analyze the relationship between temperature, light, and house with the road on the quality of life of people with DM. Methods: This study used a cross-sectional design. The sample in this study amounted to 117 people using a purposive sampling technique. It was conducted using the WHOQoL-BREF questionnaire, temperature observations with a thermohygrometer, light using a luxmeter, and the distance from house to road using a roll meter. The strength of the correlation between variables was analyzed using the Chi-Square test. Results: There was a significant relationship between bedroom temperature (p= 0.000), bedroom light (p= 0.004), family room temperature (p= 0.000), family room light (p= 0.005), and distance from house to house. roads (p = 0.000) = 0.018) with the quality of life of DM patients. Conclusion: It can be concluded that the bedroom temperature, bedroom light, family room temperature, family room light, and distance from the house to the road are not eligible can affect the quality of life of people with DM. It is recommended for the community to be able to maintain, adjust, and optimize the physical environment.